2019
DOI: 10.1016/j.ijid.2018.10.021
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of epilepsy in an onchocerciasis endemic health zone in the Democratic Republic of the Congo, despite 14 years of community-directed treatment with ivermectin: A mixed-method assessment

Abstract: HighlightsA high epilepsy prevalence in the Aketi health zone was observed despite 14 years of community-directed treatment with ivermectin.The high prevalence of OV16 antibodies in children is indicative of high ongoing onchocerciasis transmission.High onchocerciasis transmission is the consequence of high exposure to blackflies and low intake of ivermectin.Head nodding seizures were observed in 13.8% of the persons with epilepsy.Ivermectin coverage needs to be increased and bi-annual distribution should be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 23 publications
1
48
0
Order By: Relevance
“…Onchocerciasis‐associated epilepsy (OAE) and the nodding syndrome, an epileptic condition which affects children living in areas where onchocerciasis is endemic, are important entities …”
Section: Treatmentmentioning
confidence: 99%
“…Onchocerciasis‐associated epilepsy (OAE) and the nodding syndrome, an epileptic condition which affects children living in areas where onchocerciasis is endemic, are important entities …”
Section: Treatmentmentioning
confidence: 99%
“…Case-control studies NSETHIO performed four case-control studies in the DRC (Colebunders et al 2016b;Levick et al 2017;Mandro et al 2018;Mukendi et al 2019). The lesson learned from these case-control studies is that in order to determine whether onchocerciasis is a risk factor for developing epilepsy, we need to take into account previous ivermectin use as a confounder.…”
Section: Studies Performed By the Nsethio Consortium Includedmentioning
confidence: 99%
“…This could rather be because all the children in these families have been exposed to O. volvulus-infected blackflies and are more susceptible to develop OAE (Colebunders et al 2018d). Because of the clustering of PWE in families, there is a common belief in local communities, even by local health care workers, that epilepsy is contagious and transmissible by contact (Mukendi et al 2019). In Aketi, in the DRC, focus group discussions revealed that children were not accepted in schools because it was considered they could transmit the epilepsy to others.…”
Section: Qualitative Researchmentioning
confidence: 99%
“…An association between onchocerciasis (river blindness) and epilepsy was reported as early as 1938 [1]. This association was later documented in many cross-sectional studies [2][3][4][5], but the causal relationship between onchocerciasis and epilepsy remains controversial. A recent cohort study performed in an onchocerciasis-endemic region in Cameroon strongly suggested that infection with Onchocerca volvulus is able to cause epilepsy depending on the microfilarial (mf) density [6].…”
Section: Introductionmentioning
confidence: 99%